Pendekatan Tafsir Ilmi dalam Kandungan Tanaman Tin (Ficus carica L.) untuk Kesehatan Pandangan Islam dan Sains - Faizah Erica Andi Sabrina; M. Imamuddin; Umaiyatus Syarifah (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2025)
The Qur'an is an extraordinary miracle for the universe that provides guidance to humans, and contains scientific signs and information that can be verified through advances in scientific methods and discoveries in the modern era. The use of medicinal plants/herbs in healing diseases is prominent in Islamic teachings, such as the fig plant (Ficus carica L.). This research uses a qualitative descriptive method by collecting data from various library sources, including journals, books and other literature. The fig plant (Ficus carica L.) belongs to the Moraceae family and has potential as a source of bioactive chemicals. Allah has mentioned figs in Surah At-Tin verse 1 and mentioned their benefits in preventing hemorrhoids and useful for bone diseases, as conveyed in the Hadith by the Prophet Muhammad Saw., through Abu Dzar. Fig plants contain phytochemicals such as flavonoids, polyphenols, saponins, xanthol, and ꞵ-setosterol, and contain iodine, calcium, phosphorus, iron, magnesium, sulfur (phosphate), chlorine, malic acid, and nicotinic acid. Fig plants have an important role in maintaining health by fighting oxidative stress from free radicals, preventing cancer, avoiding blood vessel disease, reducing the risk of paralysis, maintaining respiratory function, reducing liver inflammation, warding off leprosy, relieving headaches, and maintaining a healthy nervous system.